Rancang Bangun Data Mining Penjualan Obat Bebas dengan Algoritma Apriori pada Apotek Kimia Farma 367 Bekasi - Imam Muttaqin; Wiga Ariani; Nur Hikmah; Delpima Suhita (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Most pharmacies that sell their merchandise have sales transaction data. Daily sales transaction data will cause data accumulation, because of the many sales transactions that occur every day. To increase sales, a pharmacy must have important information in increasing its sales, one way is to process the accumulated transaction data into useful information. This information can be used to create a business policy, namely by implementing the information into a business strategy. A pharmacy definitely needs business strategies to develop its business. In the business field, the results of implementing Data Mining with the Apriori Algorithm can help business people in making decisions about what is related to inventory.